Y chromosome AZFc microdeletion may have negative effect on embryo euploidy: a retrospective cohort study - Wei Jiang; Qijun Xie; Xin Li; Ye Yang; Ting Luan; Danyu Ni; Yuting Chen; Xinyu Wang; Chun Zhao; Xiufeng Ling (BMC, 2023)
Abstract Background Embryo aneuploidy is a main of principal reason of pregnancy loss, in vitro fertilization (IVF) failure and birth defects in offspring. Previous researchs have demonstrated that Y chromosome AZFc microdeletion was associated with reproduction outcomes, however, the relationship between Y chromosome AZFc microdeletion and embryo aneuploidy remains unexplored. Methods This retrospective cohort study enrolled 513 patients with 603 cycles in the reproductive center of Nanjing Maternity and Child Health Care Hospital from January 1, 2016 to June 30, 2022. The study cohort was divided into two groups: the AZFc microdeletion group, comprising 53 patients and 58 cycles, and the control group, comprising 460 patients and 545 cycles. Statistical methods including restricted cubic spline and generalized estimating equation (GEE) were employed to evaluate the relationship between Y chromosome AZFc microdeletion and embryo euploidy. Results 294 and 2833 blastocysts were selected as AZFc microdeletion group and control group, respectively. Patients with Y chromosome AZFc microdeletion had significantly higher embryo aneuploid rate (33.0% vs. 27.3%, P < 0.05), lower rate of normal fertilization rate (81.5% vs. 90.3%, P < 0.05) and lower blastocysts formation rate (47.0% vs. 57.8%, P < 0.05) compared with the control group. However, no significant differences in pregnancy outcomes after euploid embryos transfer were observed between these two groups. Conclusions Our study underscored the association between Y chromosome AZFc microdeletion and an elevated risk of embryo aneuploidy. Before the conventional intracytoplasmic sperm injection (ICSI) treatment, couples with Y chromosome AZFc microdeletion should be apprised of the heightened susceptibility to embryo aneuploidy. Preimplantation genetic testing for aneuploidy (PGT-A) should be introduced for selection.